Genomes Vary in Size and Spatial Patterns Within Chimeric Blades of Porphyra spp. - Varela-Álvarez, Elena; Loureiro, João; Meirmans, Patrick G.; Castro, Mariana; Serrão, Ester A. (Frontiers in Marine Science, 2021)
Genome size variation is of crucial biological importance, however variation in genome sizes within a single individual/organism is rarely reported except for some species groups such as algae where polygenomy, endopolyploidy and mixopolyploidy have previously been reported. The red algal genus Porphyra forms part of very profitable marine food products commonly known as ‘Nori’. Farming of these valuable marine crops was revolutionized by the discovery of their life cycle in the 40´s. One of the most remarkable characteristics of these taxa is the formation of chimeric gametophytic thalli. After meiosis, the four meiotic products are not released as individuals spores, but instead develop together into a single leafy thallus through successive mitotic divisions. In this study, we used flow cytometry to estimate genome sizes in 670 vegetative thallus sections from 195 blades from three Porphyra species, to determine if this chimerism could be related to the presence of multiple genome sizes and mixoploidy within thalli. Our results show a wide variety of genome sizes both within and between thalli. We interpreted these results as the presence of two different genome types of different sizes (a and b) with separate rounds of genome duplications within the vegetative thalli. By analysing several sections per thallus, we were able to show that the different genome types and ploidy levels are not distributed haphazardly through the thallus, but are distributed along the thallus in a sectorial way in mosaics. In some individuals, the 2C genome size can either be interpreted as diploids or alternatively as haploid cells that are arrested at the G2-stage of the mitotic cycle, acting as diploid with two copies of their genome during most of their life-time. We conclude that Porphyra species belong to an aneuploid/euploid system, where genome duplications, mixoploidy, chromosomal dynamics and the presence of different genome types in the chimeric thalli play a role in shaping the genetic diversity of these taxa. Our results may have important implications to understand red algae biology and evolution and raise further questions on concepts of what constitutes an individual